2006
DOI: 10.1007/s10162-006-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

Planar Relationships of the Semicircular Canals in Two Strains of Mice

Abstract: The mouse is increasingly important as a subject of vestibular research. Although many studies have focused on the vestibular responses of mice to angular rotation, the geometry of their semicircular canals has not been described. High-voltage X-ray computed tomography was used to measure the anatomy of the semicircular canals of two strains of mice, C57Bl/6J and CBA/CaJ. The horizontal plane of a stereotaxic coordinate system was defined by the midpoints of the external auditory meati and the point where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 48 publications
1
73
1
1
Order By: Relevance
“…Computations based upon our functional technique resulted in estimates of canal planes that were similar to the results from high-voltage X-ray computed tomography of the temporal bones (Calabrese and Hullar 2006).…”
Section: Geometry Of Canal Planesmentioning
confidence: 57%
“…Computations based upon our functional technique resulted in estimates of canal planes that were similar to the results from high-voltage X-ray computed tomography of the temporal bones (Calabrese and Hullar 2006).…”
Section: Geometry Of Canal Planesmentioning
confidence: 57%
“…Generally, amongst mammals, the anterior canal is larger than the posterior and lateral canals. This has been demonstrated in rats (Cummins, 1925), mice (Calabrese & Hullar, 2006), chinchillas (Hullar & Williams, 2006), little brown bats (Ramprashad et al 1980), rhesus and squirrel monkeys (Blanks et al 1985), as well as guinea pigs, cats and humans (Curthoys et al 1977). This relationship is also seen in most of the wide range of mammals studied by Ramprashad et al (1984) and the large number of primates examined by Spoor & Zonneveld (1998) although the anterior and posterior canals are often very close in size and, in some cases, the radius of the posterior canal exceeds that of the anterior canal (e.g.…”
Section: Canal Sizementioning
confidence: 67%
“…The angle of the horizontal semicircular canal is 23° upwards from L-B (Calabrese and Hullar, 2006), placing the canal during ambulation at 6° downwards from earthhorizontal. This value accords with the observation that most species position their heads so as to hold the plane of the horizontal semicircular canal horizontal.…”
Section: Natural Position Of the Head And The "Rest" Position Of The mentioning
confidence: 99%
“…It is also possible that the difference in horizontal canal inclination reflects the different mouse strains used in the two studies. The micro-CT study demonstrated significant inter-strain variation in the anatomic orientations of the semicircular canals (Calabrese and Hullar, 2006). Of particular significance, Vidal and colleagues studied the C3H strain.…”
Section: Natural Position Of the Head And The "Rest" Position Of The mentioning
confidence: 99%